Porous alumina powder as well as preparation method and application thereof

By controlling the structure and performance of porous aluminum powder, the traditional aluminum powder body is resolved in improving the lack of lithium -ion battery diaphragm absorption and liquid protection capacity, and has achieved higher battery safety and service life.

CN119349610APending Publication Date: 2025-01-24SUZHOU GINET NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411525862.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional alumina powders are limited in improving the liquid retention and liquid absorption capacity of lithium-ion battery separators, and it is difficult to meet the battery's needs for high safety, rapid liquid absorption and high liquid retention.

Method used

By controlling the specific surface area, particle size range, pore size range and surface free energy of porous alumina powder, porous alumina powder with specific structure and properties is prepared, and its pore structure and surface are optimized through hydrothermal reaction and calcination process. characteristic.

Benefits of technology

It significantly improves the liquid absorption and retention capacity of the separator, improves the overall performance of the battery, and enhances the safety and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349610A_ABST
    Figure CN119349610A_ABST
Patent Text Reader

Abstract

The invention discloses porous alumina powder as well as a preparation method and application thereof. The specific surface area of the porous alumina powder is 10m < 2 > / g-50m < 2 > / g, the particle size range is 300nm-2000nm, the aperture range is 1nm-80nm, and the surface free energy is 30mN / m-45mN / m. The performance of aluminum oxide is optimized by selecting a specific particle size range, a specific pore size range and a specific surface area, and it is required that the aluminum oxide contains a porous structure, overexposure of unsaturated aluminum ions on the surface needs to be reduced, that is, the surface free energy needs to be controlled, so that the aluminum oxide has high hydroxyl adsorption capacity, the absorption rate on a polar solvent is increased, and the service life of the aluminum oxide is prolonged. And meanwhile, the adsorption capacity of hydroxyl is not suitable to be too strong, so that the storage and the use are not influenced. Therefore, when the aluminum oxide with the structure is used for coating the diaphragm, the liquid absorption and liquid retention capabilities of the diaphragm are remarkably improved, and the comprehensive performance of the battery diaphragm is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and in particular to a porous alumina powder and a preparation method and application thereof. Background Art

[0002] As one of the four main materials of lithium-ion batteries, the diaphragm is used to separate the positive and negative electrode materials and transmit lithium ions. It can conduct ions but not electrons. At present, the battery lithium industry has higher and higher requirements for diaphragms, which require them to have high safety, fast liquid absorption and high liquid retention. At the same time, in order to increase energy density, the diaphragm needs to be made as thin as possible. However, a single polymer diaphragm is often difficult to meet the requirements. Among many technologies, the coating of ceramic materials is the best way to achieve the above requirements.

[0003] The porosity of the ceramic coating is greater than that of the diaphragm, which helps to enhance the liquid retention and wettability of the diaphragm, thereby extending the cycle life of the battery. Among the many coated ceramic materials, alumina has excellent high temperature resistance and extremely strong chemical inertness, which can greatly improve the safety of lithium-ion batteries; in addition, the alumina coating can also neutralize free HF in the electrolyte, improving the service life of the battery, and is considered to be one of the most ideal materials.

[0004] However, traditional alumina (such as the low specific surface area ultrafine alumina powder of CN202311752170.0 and the α-phase flaky nano alumina of CN202211599803.4) relies on the voids created by accumulation and capillary action to increase the liquid retention capacity of the diaphragm, which largely depends on the particle size of the powder itself and the accumulation state of the powder, and has limited effect on the improvement of the liquid absorption capacity of the diaphragm.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a porous alumina powder and a preparation method and application thereof, so as to improve the above technical problems.

[0007] The present invention is achieved in that:

[0008] In a first aspect, the present invention provides a porous alumina powder having a specific surface area of ​​10 m 2 / g~50m 2 / g, particle size range is 300nm~2000nm, pore size range is 1nm~80nm and surface free energy is 30mN / m~45mN / m.

[0009] Optionally, the D50 of the porous alumina powder is 450nm to 500nm, and the surface free energy is 35mN / m to 40mN / m.

[0010] Optionally, the crystal form of the porous alumina powder includes at least two of the γ crystal form, η crystal form, θ crystal form, δ crystal form and α crystal form.

[0011] Optionally, the water contact angle of the porous alumina powder is 75° to 85°.

[0012] Optionally, the shape of the porous alumina powder includes prisms and other irregular shapes, wherein the mass proportion of the prism-shaped porous alumina in the porous alumina powder is greater than 50%;

[0013] Optionally, in a transmission electron microscope image with a scale of less than 100 nm, the pores of the porous alumina powder show a texture with the same orientation, and the pore shape is circular or polygonal.

[0014] In a second aspect, the present invention further provides a method for preparing the porous alumina powder, which comprises:

[0015] The first hydrothermal reaction generates a precursor solution containing hydrated aluminum oxide seeds;

[0016] The second hydrothermal reaction crystal growth obtains a precursor containing layered hydrated aluminum oxide;

[0017] The precursor is calcined to obtain the porous alumina powder.

[0018] Optionally, the first hydrothermal reaction to generate a precursor solution containing hydrated aluminum oxide seeds includes: reacting an aluminum source, water, an aluminum source co-solvent and nitric acid in a hydrothermal reactor.

[0019] Optionally, the mass ratio of the aluminum source, water, aluminum source co-solvent and nitric acid is 5-10:10-20:2-10:1-3.

[0020] Optionally, the aluminum source is aluminum isopropoxide, and the aluminum source co-solvent is isopropanol.

[0021] Optionally, the total volume of the aluminum source, water, aluminum source co-solvent and nitric acid accounts for 40% to 70% of the volume of the hydrothermal reactor.

[0022] Optionally, the reaction temperature of the first hydrothermal reaction is 160° C. to 200° C., and the reaction time is 2 h to 18 h.

[0023] Optionally, the second hydrothermal reaction crystal growth to obtain a precursor containing layered hydrated aluminum oxide includes: reacting the precursor solution, aluminum hydroxide, sodium hydroxide and water in a hydrothermal reactor.

[0024] Optionally, the mass ratio of the precursor solution, aluminum hydroxide, sodium hydroxide and water is 15-45:39:10-30:22-61.

[0025] Optionally, the total volume of the precursor solution, aluminum hydroxide, sodium hydroxide and water accounts for 30% to 70% of the volume of the hydrothermal reactor.

[0026] Optionally, the reaction temperature of the second hydrothermal reaction is 180°C to 220°C.

[0027] Optionally, the calcination temperature is 500° C. to 1200° C., preferably 900° C. to 1100° C., and the calcination holding time is 2 h to 12 h.

[0028] Optionally, the heating rate of calcination is 0.5°C / min to 5°C / min.

[0029] Optionally, the precursor is washed, filtered, demagnetized and dried in sequence before calcination.

[0030] In a third aspect, the present invention also provides the use of the above-mentioned porous alumina powder in the preparation of diaphragm ceramic coatings.

[0031] In a fourth aspect, the present invention further provides a diaphragm coated with a ceramic material, wherein the ceramic material is the porous alumina powder mentioned above.

[0032] The present invention has the following beneficial effects: by selecting a specific particle size range, pore size range and specific surface area to optimize the performance of alumina, it is required to contain a porous structure while also reducing the excessive exposure of unsaturated aluminum ions on the surface, that is, it is necessary to control its surface free energy so that it has a strong hydroxyl adsorption capacity, accelerates the absorption rate of polar solvents, and obtains more liquid storage capacity, but at the same time, the hydroxyl adsorption capacity should not be too strong to affect its storage and use. Therefore, the alumina with this structure is used for the coating of the diaphragm, which significantly improves the liquid absorption and liquid retention capacity of the diaphragm and improves the comprehensive performance of the battery diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 This is a field emission electron microscope image of the porous alumina of Example 1 of the present invention;

[0035] Figure 2This is a transmission electron microscope image of the porous alumina of Example 1 of the present invention;

[0036] Figure 3 It is a comparison chart of the absorption rate and liquid absorption amount of water by the alumina powder of Example 1 of the present invention and the comparative example;

[0037] Figure 4 It is a comparison chart of the absorption rate and liquid absorption amount of n-hexane by the alumina powder of Example 1 of the present invention and the comparative example. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0039] The porous alumina powder provided by the present invention and its preparation method and application are described in detail below.

[0040] During the cycle of lithium batteries, side reactions continue to occur, forming substances such as SEI films and continuously consuming electrolytes, resulting in Li loss, increased internal resistance, etc., which ultimately affect the battery life and capacity decay. Therefore, for the diaphragm, it is necessary to improve the overall liquid retention and liquid absorption capacity of the diaphragm, so that the electrolyte can be replenished in time during the process of generating side reactions to maintain the overall performance of the battery. At present, the aluminum oxide used for coating modified diaphragms mainly relies on the particle size of the powder itself and the stacking state of the powder to improve the liquid retention and liquid absorption capacity of the diaphragm, but the improvement is limited. Based on this, the inventors have proposed the following scheme through a lot of research and practice.

[0041] Some embodiments of the present invention provide a porous alumina powder having a specific surface area of ​​10 m 2 / g~50m 2 / g, particle size range is 300nm~2000nm, pore size range is 1nm~80nm and surface free energy is 30mN / m~45mN / m.

[0042] By controlling the specific surface area, particle size range and pore size range of porous alumina, on the one hand, compared with traditional alumina powder, its specific surface area is increased, the exposed surface and unsaturated aluminum ions are increased, the corresponding surface free energy is increased and the contact angle is reduced, and the adsorption capacity of hydroxyl is also enhanced, thereby achieving an accelerated absorption rate of polar solvents, and the porous structure also enables the alumina to have a higher liquid storage capacity. On the other hand, by optimizing the controlled particle size and pore structure, it is also necessary to make the surface free energy within a specific range, that is, while requiring it to contain a porous structure, it is also necessary to reduce excessive exposure of unsaturated aluminum ions on the surface to avoid excessive adsorption of hydroxyl groups, which is not conducive to the storage and use of alumina, because the hydroxyl content on the surface of alumina increases, the water absorption increases, and then leads to an increase in its viscosity and difficulty in dispersion. After the diaphragm is coated, it is not conducive to its strength, heat shrinkage performance and absorption of electrolyte.

[0043] It should be noted that “holes” include large openings or depressions on the surface, as well as closed holes or channels inside. These channels can be through holes connected to the surface, or closed channels connecting multiple closed holes.

[0044] In some embodiments, the surface free energy of the porous alumina is 35 mN / m to 40 mN / m. The surface free energy has an important influence on the performance of porous alumina. On the one hand, the surface free energy needs to be increased to improve the wettability of the electrolyte on the diaphragm and the bonding strength between the alumina and the diaphragm matrix; on the other hand, the surface free energy needs to be controlled not to be too high to avoid excessive moisture, increased viscosity, and difficulty in dispersion, which is not conducive to the strength, heat shrinkage performance, and absorption of the electrolyte of the coated diaphragm.

[0045] In some embodiments, the water contact angle of the porous alumina powder is 75° to 85°, for example 75° to 81°. The water contact angle of the porous alumina powder is lower than that of the traditional alumina powder (non-porous), thereby improving the wettability of the electrolyte, absorbing the electrolyte more quickly, helping to reduce the internal resistance of the battery, and increasing the ion transfer rate, thereby improving the charge and discharge performance and rate performance of the battery.

[0046] In some embodiments, the D50 of the porous alumina powder is 450nm to 500nm, such as 450nm, 455nm, 460nm, 465nm, 470nm, 475nm, 480nm, 485nm, 490nm, 495nm or 500nm, or between any two of the above values. First, the ceramic particles have a small particle size and can be more densely packed during the coating process, which may reduce the porosity of the diaphragm. The reduction in porosity will make the diaphragm less wettable to the electrolyte and affect the ion transfer rate. But at the same time, it may also increase the mechanical strength of the diaphragm, making it more difficult to puncture. When the particles are larger, the porosity is relatively high, which is conducive to the storage of the electrolyte and the rapid transmission of ions. However, excessive pores may cause the mechanical strength of the diaphragm to decrease, and it is easy to break during the use of the battery. Therefore, a suitable D50 particle size is conducive to taking into account better wettability and mechanical strength. Secondly, a moderate D50 is conducive to the uniformity of the thickness of the coating. Furthermore, a moderate D50 can provide a good ion transmission channel under the premise of ensuring a certain porosity. Ions can move quickly in the pores between ceramic particles, improving ion conductivity and thus improving the charge and discharge performance of the battery. Too small or too large a D50 may affect the formation of ion transmission channels and reduce ion conductivity.

[0047] For reference, in some embodiments, the crystal form of the porous alumina powder includes at least two of the γ crystal form, the η crystal form, the θ crystal form, the δ crystal form and the α crystal form. Alumina of various crystal forms is beneficial to improving its comprehensive performance as a ceramic coating material, and different crystal forms of alumina have different surface active sites, which can interact with various components in the electrolyte to varying degrees, regulate ion transport, improve electrolyte interface stability, etc.

[0048] In some embodiments, the shape of the porous alumina powder includes prisms and other irregular shapes, wherein the mass proportion of the prismatic porous alumina in the porous alumina powder is greater than 50%. The content of prismatic porous alumina is relatively large, which is conducive to providing a more ordered ion transmission channel and facilitating the migration of lithium ions in the diaphragm, thereby improving the rate performance and charge and discharge efficiency of the battery. In addition, it is also conducive to enhancing mechanical strength, improving thermal stability, and optimizing electrode-diaphragm interface performance.

[0049] Further, in some embodiments, in the transmission electron microscope image with a scale of less than 100nm, the pores of the porous alumina powder show the same texture in the same direction, and the pore shape is circular or polygonal. It can be seen that the size, shape and distribution of the pores of the porous alumina provided in the embodiment of the present invention are relatively uniform. This makes the transmission path of lithium ions in the diaphragm more regular and consistent, reduces the obstruction and scattering during ion transmission, thereby improving the ion transmission efficiency, and helps the battery to achieve better charge and discharge performance, especially in the case of high-rate charge and discharge, it can ensure that the battery is charged and discharged quickly and stably. At the same time, the uniform pore structure can make the diaphragm more uniform in stress distribution when it is subjected to external forces (such as pressure during battery assembly, expansion and contraction of electrode materials, etc.), and it is not easy to cause structural damage or pore deformation caused by local stress concentration. This can effectively maintain the integrity and stability of the diaphragm, reduce the risk of safety problems such as internal short circuits caused by changes in the diaphragm structure, and improve the reliability and safety of the battery. In addition, the texture texture in the same direction is conducive to the uniform penetration and distribution of the electrolyte in the diaphragm. The electrolyte can be fully filled into each pore and fully contact the alumina ceramic material, improving the diaphragm's ability to absorb and retain electrolyte, thereby improving the battery's cycle performance and service life. In addition, consistent wettability can ensure that the diaphragm's ability to retain electrolyte is relatively stable under different battery operating conditions, reducing local battery performance degradation caused by uneven electrolyte distribution.

[0050] Furthermore, some embodiments of the present invention also provide a method for preparing the porous alumina powder, which comprises:

[0051] S1. The first hydrothermal reaction generates a precursor solution containing hydrated alumina seeds.

[0052] Specifically, in some embodiments, an aluminum source, water, an aluminum source co-solvent and nitric acid are reacted in a hydrothermal reactor.

[0053] For reference, the mass ratio of the aluminum source, water, aluminum source co-solvent and nitric acid is 5-10:10-20:2-10:1-3.

[0054] In some embodiments, the aluminum source is aluminum isopropoxide, and the aluminum source co-solvent is isopropanol.

[0055] In some embodiments, the total volume of the aluminum source, water, aluminum source co-solvent and nitric acid accounts for 40% to 70% of the volume of the hydrothermal reactor, for example 40%, 45%, 50%, 55%, 60%, 65% or 70%, or between any two of the above percentages.

[0056] In some embodiments, the reaction temperature of the first hydrothermal reaction is 160°C to 200°C, for example 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C, etc., or between any two of the above temperatures, and the reaction time is 2h to 18h, for example 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h or 18h, etc., or between any two of the above temperatures. It should be noted that, generally speaking, the higher the reaction temperature, the shorter the corresponding reaction time.

[0057] By selecting the above reaction raw materials and reaction conditions, a hydrated aluminum oxide seed solution can be generated as a precursor solution through the first hydrothermal reaction.

[0058] In some embodiments, aluminum isopropoxide, water, isopropanol, and nitric acid are put into a hydrothermal reactor in a mass ratio of 10:20:3:2, and the overall volume accounts for 40% to 70%; the temperature is increased to 180°C at a heating rate of 5°C / min, and the reaction is carried out for 2 to 18 hours to obtain a reaction product precursor solution A, i.e., a hydrated aluminum oxide seed solution.

[0059] S2. The second hydrothermal reaction crystallizes and grows to obtain a precursor containing layered hydrated aluminum oxide.

[0060] Specifically, in some embodiments, the precursor solution obtained in S1 is reacted with aluminum hydroxide, sodium hydroxide and water in a hydrothermal reactor.

[0061] In some embodiments, the mass ratio of the precursor solution, aluminum hydroxide, sodium hydroxide and water is 15-45:39:10-30:22-61.

[0062] In some embodiments, the total volume of the precursor solution, aluminum hydroxide, sodium hydroxide and water accounts for 30% to 70% of the volume of the hydrothermal reactor, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, or between any two of the above percentages.

[0063] In some embodiments, the reaction temperature of the second hydrothermal reaction is 180°C to 220°C, for example 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C or 220°C, etc., or between any two of the above temperatures, and the reaction time is 6h to 24h, for example 6h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h or 18h, 19h, 20h, 21h, 22h, 23h or 24h, etc., or between any two of the above temperatures. It should be noted that, generally speaking, the higher the reaction temperature, the shorter the corresponding reaction time.

[0064] By selecting the raw materials and controlling the reaction conditions in the above manner, crystal growth is performed on the basis of the hydrated alumina seeds in the precursor solution to obtain layered hydrated alumina as a calcined precursor.

[0065] In some embodiments, precursor solution A, aluminum hydroxide, sodium hydroxide, and water are put into a hydrothermal reactor in a mass ratio of 20:39:11:50, and the overall volume accounts for 30% to 70%; the temperature is increased to 180°C to 220°C at a heating rate of 5°C / min, and the reaction is carried out for 6 to 24 hours to obtain precursor B.

[0066] S3, calcining the precursor obtained in step S2 to obtain the porous alumina powder.

[0067] During the calcination process, the precursor loses water and produces unsaturated oxygen ions and gaps. In order to maintain the charge conservation inside the crystal, the surrounding aluminum ions and oxygen ions diffuse to fill these gaps, leaving their original positions, causing lattice distortion to form expansion and contraction sites; with the continuous departure of water molecules and the continuous diffusion of aluminum and oxygen ions, new phases are formed while the interior of the grains shrinks to form gaps, which gradually turn into holes; under low temperature conditions, water loss and hole formation occur gradually from the surface to the inside, and this reaction occurs evenly at any part of the surface. The pores formed are small and dense, which increases the specific surface area sharply.

[0068] Specifically, in some embodiments, the calcination temperature is 500°C to 1200°C, for example 500°C, 600°C, 650°C, 700°C, 800°C, 850°C, 900°C, 1000°C, 1100°C or 1200°C, or between any two of the above temperatures, preferably 900°C to 1100°C, and the calcination holding time is 2h to 12h, for example 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, etc. Generally speaking, the higher the calcination temperature, the shorter the holding time.

[0069] It should be noted that the choice of calcination temperature is very important for the formation of the pore structure of porous alumina. If the calcination temperature is too low, it will easily lead to smaller pore size and relatively uneven distribution, and the specific surface area and surface free energy will not meet the expected standards. If the calcination temperature is too high, the pore size will be too large and the distribution will become narrower. It is also easy to produce melting, resulting in a large number of pores being compressed and closed, thereby reducing the storage of electrolyte and reducing ion transmission channels.

[0070] In some embodiments, the heating rate of calcination is 0.5°C / min to 5°C / min, for example, 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min, etc.

[0071] In some embodiments, the layered hydrated alumina precursor is sequentially washed, filtered, demagnetized and dried before calcination.

[0072] In some embodiments, the precursor B is washed, filtered, demagnetized, dried, and calcined to obtain porous alumina. The heating rate of calcination is between 0.5°C / min and 5°C / min, the calcination temperature is between 500°C and 1200°C, and the holding time is between 2h and 12h.

[0073] Some embodiments of the present invention also provide the use of the porous alumina powder in preparing a diaphragm ceramic coating.

[0074] Some embodiments of the present invention also provide a diaphragm coated with a ceramic material, wherein the ceramic material is the porous alumina powder.

[0075] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0076] The following examples and comparative examples were tested for surface free energy and water contact angle using the Washburn method.

[0077] The surface tension was measured by Tensiio mechanical surface tension tester.

[0078] Weigh the same mass of powder; put the powder into a glass test tube with an open bottom and lined with filter paper, and hang the test tube on the scale of the test instrument; select different test solvents (water, n-hexane), load them into the test bench, and then slowly raise the test bench to under the glass test tube, and use the program to record the change in mass over time after the page contacts the glass test tube.

[0079] According to the relationship between the mass of liquid adsorbed by the powder and the time, the contact angle between the powder and the liquid is tested. The smaller the contact angle, the better the wettability.

[0080] The surface free energy and contact angle were calculated using the following formula:

[0081]

[0082] Where m is the liquid absorption mass of the test sample, t is the flow time, δ is the surface tension, c is the capillary constant, ρ is the liquid density, θ is the contact angle, and η is the liquid viscosity.

[0083] The following examples and comparative examples adopt the laser particle size test analysis method, according to the standard of GB / T 19077-2016, through the laser particle size tester Mastersizer3000 A range of particle sizes were tested.

[0084] The following examples and comparative examples adopt X-ray diffraction method, and according to the standard of GB / T 30904-2014, the crystal structure is tested by X-ray diffractometer Bruker AXS-D8 Advance.

[0085] The following examples and comparative examples adopt the gas adsorption BET method, and the specific surface area and pore size range are tested by a specific surface tester Micromeritics-3020Ⅱ according to the standard of GB / T 6609.35-2023.

[0086] Example 1

[0087] This embodiment provides a porous aluminum oxide, which is prepared by the following preparation method:

[0088] (1) Synthesis of precursor solution A: Aluminum isopropoxide, water, isopropanol, and nitric acid are placed in a hydrothermal reactor at a mass ratio of 10:10:5:2, with the total volume accounting for 60%; the temperature is increased to 180°C at a heating rate of 5°C / min, and the reaction is carried out for 12 hours to obtain the reaction product precursor solution A. Hydrated aluminum oxide seed crystals

[0089] (2) Synthesis of Precursor B: Precursor solution A, aluminum hydroxide, sodium hydroxide, and water were added into a hydrothermal reactor in a mass ratio of 25:39:15:30, with the overall volume accounting for 60%; the temperature was raised to 200°C at a heating rate of 5°C / min, and the reaction was carried out for 24 hours to obtain Precursor B. Crystal growth (layered)

[0090] (3) Synthesis of porous alumina: Precursor B is washed, filtered, demagnetized, dried, and calcined to obtain porous alumina. The heating rate of calcination is 3°C / min, the calcination temperature is 1000°C, and the holding time is 4h.

[0091] The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. Its specific surface area is 21.12 m 2 / g, particle size D50 = 0.49um; pore size 9.52nm, crystal forms include α, γ and δ phases; surface free energy is 36.15mN / m, water contact angle is 80.118°.

[0092] The porous alumina was observed by field emission electron microscopy, and the electron microscope image is as follows: Figure 1 As shown, from Figure 1 It can be seen that the porous alumina is composed of more than 50% prisms and other irregular bodies. The porous alumina was observed by transmission electron microscopy, and the results are as follows: Figure 2 As shown, in the transmission electron microscope image with a scale of less than 100 nm, the texture with the same orientation represented by the arrangement of the channels can be clearly observed, and the pore shape is circular or polygonal.

[0093] Example 2

[0094] The difference between this embodiment and embodiment 1 is that the mass ratio of aluminum isopropoxide, water, isopropanol and nitric acid is adjusted to 5:10:5:2.

[0095] The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. Its specific surface area is 18.23 m 2 / g, particle size D50 = 0.63um; pore size 9.43nm, crystal forms including α, γ and δ phases; surface free energy 34.63mN / m, water contact angle 81.374°.

[0096] Example 3

[0097] The difference between this embodiment and embodiment 1 is that the mass ratio of aluminum isopropoxide, water, isopropanol and nitric acid is adjusted to 10:20:5:2.

[0098] The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. Its specific surface area is 19.71 m 2 / g, particle size D50 = 0.59um; pore size 9.71nm, crystal forms including α, γ and δ phases; surface free energy 35.57mN / m, water contact angle 81.006°.

[0099] Example 4

[0100] The difference between this embodiment and embodiment 1 is that the mass ratio of precursor solution A, aluminum hydroxide, sodium hydroxide and water is adjusted to 45:39:15:30.

[0101] The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. Its specific surface area is 27.37 m 2 / g, particle size D50 = 0.33um; pore size 9.02nm, crystal forms include α, γ and δ phases; surface free energy is 38.94mN / m, water contact angle is 78.217°.

[0102] Example 5

[0103] The difference between this embodiment and embodiment 1 is that the mass ratio of precursor solution A, aluminum hydroxide, sodium hydroxide and water is adjusted to 15:39:15:22.

[0104] The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. Its specific surface area is 15.85 m 2 / g, particle size D50 = 0.84um; pore size 9.37nm, crystal forms including α, γ and δ phases; surface free energy 33.28mN / m, water contact angle 82.588°.

[0105] Example 6

[0106] The difference between this embodiment and embodiment 1 is that the mass ratio of precursor solution A, aluminum hydroxide, sodium hydroxide and water is adjusted to 15:39:30:30.

[0107] The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. Its specific surface area is 22.48 m 2 / g, particle size D50 = 0.42um; pore size 9.55nm, crystal forms including α, γ and δ phases; surface free energy 36.53mN / m, water contact angle 80.518°.

[0108] Example 7

[0109] The difference between this embodiment and embodiment 1 is that the mass ratio of precursor solution A, aluminum hydroxide, sodium hydroxide and water is adjusted to 25:30:15:61.

[0110] The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. Its specific surface area is 23.88 m 2 / g, particle size is D50=0.40um; pore size is 9.15nm, crystal forms include α, γ and δ phases; surface free energy is 37.03mN / m, water contact angle is 79.192°.

[0111] Example 8

[0112] The difference between this embodiment and embodiment 1 is that the calcination temperature is adjusted to 750°C.

[0113] The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. Its specific surface area is 37.24 m 2 / g, particle size D50 = 0.48um; pore size 6.35nm, crystal forms including γ, η and θ phases; surface free energy 39.67mN / m, water contact angle 76.974°.

[0114] Comparative Example 1

[0115] This comparative example provides a non-porous aluminum oxide with a D50 of 500 nm, which is purchased from Shandong Guoci SA0-030E;

[0116] Comparative Example 2

[0117] In this comparative example, hydrated alumina purchased from Zhongtianli New Materials Co., Ltd. was calcined through step (3) of Example 1. The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. The specific surface area was 167.18 m 2 / g, particle size D50 = 4.24um; pore size 29.83nm, crystal form including γ and δ phases; surface free energy 62.13mN / m, water contact angle 72.045°. The huge specific surface area and excessive particle size make it unsuitable for lithium battery diaphragm coating.

[0118] Comparative Example 3 The difference between this comparative example and Example 1 is that the calcination temperature is adjusted to 1200°C.

[0119] The porous alumina was tested for specific surface area, particle size range, pore size range, crystal form, surface free energy and water contact angle. Its specific surface area is 4.34 m 2 / g, particle size is D50=0.48um; pore size is 6.52nm, crystal form is α phase; surface free energy is 28.33mN / m, water contact angle is 85.113°.

[0120] The liquid absorption rate and liquid absorption amount of the porous alumina of Example 1 and the alumina of Comparative Example 1 were also directly measured using the Washburn method and the Tensiio mechanical method surface tension tester; the results are shown in Table 1 and Figure 3-Figure 4 As shown by Figure 3 and Figure 4 It can be seen that due to the increase in surface free energy, the corresponding polar part also increases, and the absorption rate and amount of water by porous alumina are significantly higher than those of ordinary alumina; and for the non-polar solvent n-hexane, porous alumina shows an absorption rate equivalent to that of ordinary alumina, but due to its porous structure, its absorption amount of n-hexane is higher than that of ordinary alumina.

[0121] Table 1 Surface energy of alumina powder and its water absorption amount and absorption rate

[0122]

[0123]

[0124] In summary, in the embodiment of the present invention, the vacancies left by the departure of water molecules during the calcination process are supplemented by the diffusion of nearby aluminum ions and oxygen ions, so that the lattice distortion that is continuously generated gradually forms pores, and the pore size increases continuously with the increase of temperature, which is conducive to increasing the amount of liquid absorbed by the powder to the solution. The pore structure of porous alumina and the larger specific surface area and the increase of exposed aluminum ions increase its surface energy and contact angle, and increase the adsorption rate of polar solvents. In addition, by controlling its surface free energy, it has a strong hydroxyl adsorption capacity, accelerates the absorption rate of polar solvents, and obtains more liquid storage capacity, but at the same time, the hydroxyl adsorption capacity should not be too strong to affect its storage and use.

[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A porous alumina powder, characterized in that: The specific surface area of ​​the porous alumina powder is 10 m 2 / g~50m 2 / g, particle size range is 300nm~2000nm, pore size range is 1nm~80nm and surface free energy is 30mN / m~45mN / m.

2. The porous alumina powder according to claim 1, characterized in that: The D50 of the porous alumina powder is 450nm-500nm, and the surface free energy is 35mN / m-40mN / m.

3. The porous alumina powder according to claim 1, characterized in that: The porous alumina powder comprises at least two of the γ crystal form, the η crystal form, the θ crystal form, the δ crystal form and the α crystal form; And / or, the water contact angle of the porous alumina powder is 75° to 85°.

4. The porous alumina powder according to any one of claims 1 to 3, characterized in that: The shape of the porous alumina powder includes prism and other irregular shapes, wherein the mass proportion of the prism-shaped porous alumina in the porous alumina powder is greater than 50%; And / or, in a transmission electron microscope image with a scale of less than 100 nm, the pores of the porous alumina powder show a texture with the same orientation, and the pore shape is circular or polygonal.

5. A method for preparing the porous alumina powder according to any one of claims 1 to 4, characterized in that: It includes: The first hydrothermal reaction generates a precursor solution containing hydrated aluminum oxide seeds; The second hydrothermal reaction crystal growth obtains a precursor containing layered hydrated aluminum oxide; The precursor is calcined to obtain the porous alumina powder.

6. The method for preparing porous alumina powder according to claim 5, characterized in that: The first hydrothermal reaction to generate a precursor solution containing hydrated aluminum oxide seeds includes: reacting an aluminum source, water, an aluminum source co-solvent and nitric acid in a hydrothermal reactor; Preferably, the mass ratio of the aluminum source, the water, the aluminum source co-solvent and the nitric acid is 5-10:10-20:2-10:1-3; Preferably, the aluminum source is aluminum isopropoxide, and the aluminum source cosolvent is isopropanol; Preferably, the total volume of the aluminum source, the water, the aluminum source co-solvent and the nitric acid accounts for 40% to 70% of the volume of the hydrothermal reactor; Preferably, the reaction temperature of the first hydrothermal reaction is 160° C. to 200° C., and the reaction time is 2 h to 18 h.

7. The method for preparing porous alumina powder according to claim 6, characterized in that: The second hydrothermal reaction crystal growth to obtain a precursor containing layered hydrated aluminum oxide includes: reacting the precursor solution, aluminum hydroxide, sodium hydroxide and water in a hydrothermal reactor; Preferably, the mass ratio of the precursor solution, the aluminum hydroxide, the sodium hydroxide and the water is 15-45:39:10-30:22-61; Preferably, the total volume of the precursor solution, the aluminum hydroxide, the sodium hydroxide and the water accounts for 30% to 70% of the volume of the hydrothermal reactor; Preferably, the reaction temperature of the second hydrothermal reaction is 180° C. to 220° C., and the reaction time is 6 h to 24 h.

8. The method for preparing porous alumina powder according to any one of claims 5 to 7, characterized in that: The calcination temperature is 500°C to 1200°C, preferably 900°C to 1100°C, and the calcination holding time is 2h to 12h; Preferably, the heating rate of calcination is 0.5°C / min to 5°C / min; Preferably, the precursor is washed, filtered, demagnetized and dried in sequence before calcination.

9. Use of the porous alumina powder according to any one of claims 1 to 4 in the preparation of diaphragm ceramic coatings.

10. A diaphragm, characterized in that: It is coated with a ceramic material, and the ceramic material is the porous alumina powder according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • A method for preparing alpha-phase flaky nano-alumina

    CN115784279B

  • Preparation method of superfine alumina powder with low specific surface area

    CN117735582A

Cited By

  • Alkaline electrolyzed water composite diaphragm based on hydroxyl alumina and preparation method of alkaline electrolyzed water composite diaphragm

    CN121556087A

  • Alumina oxyhydroxide-based alkaline electrolytic water composite separator and method for preparing the same

    CN121556087B